The effects of specific Saccharomyces cerevisiae strains and monensin supplementation on rumen fermentation in vitro - Cloete, T.E. (Thomas Eugene), 1958- (University of Pretoria, 2013)
Dissertation (MSc(Agric))--University of Pretoria, 2008.